Multi-Scenario Land Use Simulation and Land Use Conflict Assessment Based on the CLUMondo Model: A Case Study of Liyang, China - Xiangnan Fan; Yuning Cheng; Yicheng Li (Land, 2023)
By predicting and analyzing regional land use conflicts (LUCs), the contradictory relationship between urban development and land resources can be revealed, which can assist in achieving the rational use of land resources. Taking Liyang as a case study, this paper simulated land use in 2030 under three scenarios, namely, the natural growth scenario (NGS), economic development scenario (EDS), and ecological protection scenario (EPS), using the CLUMondo model. The ecological risk assessment model was used to measure the LUCs under each scenario. Through the comprehensive analysis of land use conversion, spatial distribution, and the change characteristics of LUCs, optimization strategies for future land use are proposed. The results indicate that (1) the intensity of land conversion under the three scenarios is ranked as EDS > NGS > EPS; (2) there is little change in the LUCs under the EPS, while significant deterioration is observed under the NGS and EDS; (3) the intensity of LUCs is positively correlated with the degree of land use conversion; and (4) in the future, particular attention should be paid to areas around the city center, the Caoshan Development Zone in the northwest, and Nanshan Bamboo Sea in the south, where high-intensity land use conflicts may occur.